Bcl11b/Ctip2 in Skin, Tooth, and Craniofacial System - Daher, Marie-Thérèse; Bausero, Pedro; Agbulut, Onnik; Li, Zhenlin; Parlakian, Ara (Frontiers in Cell and Developmental Biology, 2020)
Ctip2/Bcl11b is a zinc finger transcription factor with dual action (repression/activation) that couples epigenetic regulation to gene transcription during the development of various tissues as well as induces a variety of physiological responses under healthy and pathological conditions. Its role and mechanisms of action are best characterised in the immune and nervous systems. However, its implication in the development and homeostasis of other various tissues has also been reported. In the present review, we detail its role in skin development, adipogenesis, tooth formation and in cranial suture ossification. Experimental data from several studies demonstrate the involvement of Bcl11b in the control of the balance between cell proliferation and differentiation during organ formation and repair, and more specifically in the context of stem cell self-renewal and fate determination. The impact of mutations in the coding sequences of Bcl11b on the development of diseases such as craniosynostosis is also presented. Finally, we mention genome-wide association studies that suggest a potential influence of single nucleotide polymorphisms found in the 3’ regulatory region of Bcl11b on the homeostasis of the cardiovascular system.